2019
DOI: 10.3390/cells8070641
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Kinetic Analyses of Circulating Tumor Cells as Predictive Markers of Treatment Response in Locally Advanced Rectal Cancer Patients

Abstract: Neoadjuvant chemoradiation (NCRT) followed by total mesorectal excision is the standard treatment for locally advanced rectal cancer (LARC). To justify a non-surgical approach, identification of pathologic complete response (pCR) is required. Analysis of circulating tumor cells (CTCs) can be used to evaluate pCR. We hypothesize that monitoring of thymidylate synthase (TYMS) and excision repair protein, RAD23 homolog B (RAD23B), can be used to predict resistance to chemotherapy/radiotherapy. Therefore, the aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 48 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…TYMS is a rate-limiting enzyme, which plays an important role in regulating the pyrimidine metabolism signaling pathway ( Yeh et al, 2017 ). TYMS is overexpressed frequently in different kinds of cancers, such as NSCLC, pancreatic, colorectal, and breast cancers, and it has resulted in a poor cancer prognosis and chemotherapy resistance via dysregulating pyrimidine metabolism ( TroncarelliFlores et al, 2019 ; Wu et al, 2019 ). In our study, we constructed a six-gene signature for a prognostic model based on the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…TYMS is a rate-limiting enzyme, which plays an important role in regulating the pyrimidine metabolism signaling pathway ( Yeh et al, 2017 ). TYMS is overexpressed frequently in different kinds of cancers, such as NSCLC, pancreatic, colorectal, and breast cancers, and it has resulted in a poor cancer prognosis and chemotherapy resistance via dysregulating pyrimidine metabolism ( TroncarelliFlores et al, 2019 ; Wu et al, 2019 ). In our study, we constructed a six-gene signature for a prognostic model based on the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of CTCs in LARC patients undergoing nCRT followed by surgery has been explored by evaluating the predictive values of the enzyme thymidylate synthase (TYMS), the main target of 5-FU and the ultraviolet excision repair protein, RAD23 homolog B (RAD23B) before and after nCRT [ 114 ]. This study revealed that TYMS mRNA and/or TYMS/RAD23B protein expression in CTCs have the potential to predict non-response to nCRT and avoid unnecessary radical surgery for LARC patients with pCR [ 114 ].…”
Section: Circulating Biomarkers To Predict Response To Ncrt In Larmentioning
confidence: 99%
“…It enabled them to detect in isolated CTCs two molecules increasing chemotherapy and radiotherapy resistance: thymidylate synthase (TYMS) and excision repair protein RAD23 homolog B (RAD23B). Interestingly, CTCs in all patients with pCR after CRT had undetectable expression of both TYMS and RAD23B [58].…”
Section: Circulating Biomarkers In Rectal Cancermentioning
confidence: 99%